Pengaruh Suhu terhadap Rendemen dan Nilai Kalor Minyak Hasil Pirolisis Sampah Plastik - Wirawan Widya Mandala; M Sigit Cahyono; Syamsul Ma`arif; H B Sukarjo; Wardoyo Wardoyo (Jurnal Mekanika dan Sistem Termal, 2016)
Plastic waste is one type of waste that would disturb the environment if it is not handled properly. Alternative treatment to solve this problem is by using pyrolysis technology that enable to convert plastic waste into fuel oil, charcoal, and non-condensable gas. The success of pyrolysis technology is influenced by several factors, including the type of reactor, the particle size, the processing time, and the temperature of the pyrolysis process. The purpose of this study was to determine the effect of temperature on the yield and the calorific value of plastic pyrolysis oil. Based on the experiments, increasing the temperature, the yield of the oil produced and calorific value will be higher. The yield and the highest calorific value generated for the pyrolysis process at a temperature of 400 0C, are 44% and 10,292 cal/ g respectively.